Quantitative analysis of agricultural land use change in China. (2015) - Chou, Jieming; Dong, Wenjie; Wang, Shuyu; Fu, Yuqing
Highlights: We explored the extent of agricultural land use and the potential of land in China. Crop sown area and potential multiple cropping index are used as index to analyze the quantitative change. The effects of climate change on the coverage of agriculture land are evaluated. We analyzed the agricultural land was affected by both natural and social factors. Abstract: This article reviews the potential impacts of climate change on land use change in China. Crop sown area is used as index to quantitatively analyze the temporal–spatial changes and the utilization of the agricultural land. A new concept is defined as potential multiple cropping index to reflect the potential sowing ability. The impacting mechanism, land use status and its surplus capacity are investigated as well. The main conclusions are as following; 1. During 1949–2010, the agricultural land was the greatest in amount in the middle of China, followed by that in the country's eastern and western regions. The most rapid increase and decrease of agricultural land were observed in Xinjiang and North China respectively, Northwest China and South China is also changed rapid. The variation trend before 1980 differed significantly from that after 1980. 2. Agricultural land was affected by both natural and social factors, such as regional climate and environmental changes, population growth, economic development, and implementation of policies. In this paper, the effects of temperature and urbanization on the coverage of agriculture land are evaluated, and the results show that the urbanization can greatly affects the amount of agriculture land in South China, Northeast China, Xinjiang and Southwest China. 3. From 1980 to 2009, the extent of agricultural land use had increased as the surplus capacity had decreased. Still, large remaining potential space is available, but the future utilization of agricultural land should be carried out with scientific planning and management for the sustainable development.